Sintering and Electrical Conductivity of Medium- and High-Entropy Calcium-Doped Four B-Site Cation Perovskite Materials - Geoffrey Swift; Sai Ram Gajjala; Rasit Koc (Crystals, 2025)
La1−xCax(Co0.25Cr0.25Fe0.25Ni0.25)O3−δ perovskite powders were prepared via a sol-gel process. The A-site was doped with calcium, while four elements—cobalt, chromium, iron, and nickel—in equiatomic amounts made up the B-site. The configurational entropy was calculated to increase with the addition of calcium from medium to high entropy. The synthesized powders were heated to 1400 °C in air for 2 h to sinter them. The effect of doping on the resulting sintered materials was observed via density measurements and electron microscopy. The electrical conductivity was measured in air as a function of temperature to 900 °C. Conductivity versus composition indicates that an increase in entropy has a marked effect on electrical conductivity, leading to two distinct relationships with temperature.